A study of progressive muscular atrophy: with special reference to the idiopathic form; and clinical notes of two cases of the latter variety - Dow, David Robert (The University of Edinburgh, 1895)
From the description which has been given of the Idiopathic Muscular Atrophies, 'it will he seen that there exist several types, all characterised; by a progressive wasting of a greater or less number of the voluntary muscles of the body, but which, at the sane time, present differences in their clinical features.

Three principal types have been selected as being most pronounced in their characters, and in this way the points of agreement and difference are more clearly brought out.

These points of difference constitute, according to some, sufficient ground for regarding the various types as distinct primary muscular affections, and not as essentially one disease, as the numerous points of agreement would more readily lead one to believe them to be.

The differences are, it must be remembered, merely differences of degree of the morbid process and in the initial localisation, both of which seem to be influenced by the date of onset.

Thus, when the disease shows itself in the early period of development, it is more apt to be attended by hypertrophy, especially in the legs and face; but when the onset occurs at a late period, wasting, especially at the roots of the limbs, is the conspicuous feature.

But it has been mentioned under the pseudo-hypertrophic form that atrophy is almost as important a feature in the disease as hypertrophy, and that the latter was due to a fatty infiltration. This fatty infiltration is also marked in the face in the Orbicularis Oris, which is always first affected, and which gives to the lips the volume they possess. Thus it may be look upon as a phase of the pseudo-hypertrophic form.

The infantile form, again, affects more frequently the male sex, and, as in the pseudo-hypertrophic form, we find transmission occurring more usually through the mother.

Many observers in recording cases of the pseudo-hypertrophic form, speak of the stupid-expression worn by these patients, even in cases in which the intelligence was undoubtedly unimpaired, and this, no doubt, was due to the greater or less implication of the muscles of the face, and the imperfect performance of their functions.